2016
DOI: 10.1021/acs.est.6b02534
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Fecal Indicators from Beach Sand to the Surf Zone by Recirculating Seawater: Laboratory Experiments and Numerical Modeling

Abstract: Recirculating seawater is an important component of submarine groundwater discharge, yet its role in transporting microbial contaminants from beach sand to coastal water is unknown. This study investigated the extent to which recirculating seawater carries fecal indicators, Enterococcus and bird-associated Catellicoccus, through the beach subsurface. Laboratory experiments and numerical modeling were performed to characterize the transport of fecal indicators suspended in seawater through medium-grained beach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Moving air‐water interfaces occur frequently in beach sand, where tidal movement of seawater causes periodic imbibition and drainage of seawater through beach sand, as well as capillary fringe fluctuations at the vadose zone‐groundwater table interface [ Russell et al ., ]. Beach sands often contain bacteria [ Yamahara et al ., ], which can be mobilized and transported through the action of moving air‐water interfaces [ Russell et al ., ; Boehm et al ., ; Brown and Boehm , ].…”
Section: Colloid Transport In Unsaturated Porous Mediamentioning
confidence: 99%
“…Moving air‐water interfaces occur frequently in beach sand, where tidal movement of seawater causes periodic imbibition and drainage of seawater through beach sand, as well as capillary fringe fluctuations at the vadose zone‐groundwater table interface [ Russell et al ., ]. Beach sands often contain bacteria [ Yamahara et al ., ], which can be mobilized and transported through the action of moving air‐water interfaces [ Russell et al ., ; Boehm et al ., ; Brown and Boehm , ].…”
Section: Colloid Transport In Unsaturated Porous Mediamentioning
confidence: 99%
“…In this regard, geographic distance has also been found to play a certain role in controlling the spatial distribution of sand microbial assemblages, suggesting that dispersal limitations may affect sand microbial communities as well [8,13]. In addition, disturbances like wave-or tidal-action may lead to the random dispersal of microbes between seawater and intertidal sands, or across the unsaturated zone of beach aquifers [2,14,15]. However, little is known about the relative importance of different ecological processes (e.g., environmental filtering and dispersal-related mechanisms) in determining the assembly of sand microbial communities, and their key ecological groups (e.g., habitat generalists and specialists).…”
Section: Introductionmentioning
confidence: 99%
“…FIB may be transported through the beach sand matrix and across the sand-water continuum via two general pathways: through-beach or over-beach. Through-beach transport of FIB, including their distribution in the subsurface and potential transport to surface waters via groundwater discharge is governed by infiltration and exfiltration (water flowing into, through and out of the unsaturated and saturated portions of the beach face); interstitial flows; and FIB-sediment interactions (which include attachment, detachment and straining) (Bradford et al 2014, Brown and Boehm 2016, Molnar et al 2015, Solo-Gabriele et al 2016. Air-water interfaces can also affect FIB transport in the vadose zone, as FIB movement may be limited by thin water films and their associated physical restrictions to flow (Flury andQiu 2008, Wan andTokunaga 1997).…”
Section: Cruising: Mechanisms Of Transportmentioning
confidence: 99%
“…In addition, using shotgun sequencing, Mohiuddin et al (2017) showed a greater taxonomic diversity in the supratidal sand than in adjacent surface water and Staley and Sadowsky (2016) showed that backshore sands had microbial communities distinct from those in nearshore sands. These findings may be because of lower moisture content in the supratidal sand compared to intertidal sands, which limit the survival of protozoan predators (Whitman et al 2014), along with various endogenous sources such as bird fecal droppings (Brown and Boehm 2016).…”
Section: Tidesmentioning
confidence: 99%
See 1 more Smart Citation